Хятадын эмгэнэлт “Aянгат бороо” жүжгийн үйл явдал хийгээд дүрүүдийг задлан шинжлэхүй: Analysis on the Events and Characters of Chinese Tragic Drama “The Thunderstorm” - B., Gerelt-Ireedui (Mongolian Journal of Foreign Languages and Cultures, 2023)
Cao Yu, a well-known contemporary Chinese playwright, wrote the four-act stage play "The thunderstorm", in 1933 which depicts the social situation in China before and after 1923, a period of great change in Chinese society. In this article, we aim to analyze the events and characters of the play. The analysis and synthesis method was firstly used to analyze the relationships, attitudes, and actions between the main and supporting characters, and from their interactions, analyzes their personalities, inner thoughts, attitudes, and natures, and then summarized them. The characters, their destinies, their personalities, their inner worlds and worldviews, their relationships and conflicts in “The thunderstorm” are really complex. In the play, Zhou and Lu tell the tragic story and sin of the family of an old Chinese society through the complexities of the lives of eight people from two families 30 years ago and after. During this time, both the Zhou and Lu families underwent changes, and as the older members grew older, they also changed mentally, creating new conflicts between them.